2018
DOI: 10.1007/s11695-018-3358-x
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term 4-Year Outcomes with Single Anastomosis Duodenal-Ileal Bypass with Sleeve Gastrectomy Surgery at a Single US Center

Abstract: SADI-S is a safe and effective procedure in both short- and mid-term data points. Diabetes resolution and weight loss appear similar to traditional RYDS and better than RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 34 publications
4
21
2
2
Order By: Relevance
“…These results continue in other studies without significant weight regain out to 4 years. In our study, especially in the patients with preoperative BMI of 45 to 55 kg/m 2 , the EWL at 12 and 24 months were 81.2% and 86.2%, respectively, and were similar to the study by Zaveri et al [36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results continue in other studies without significant weight regain out to 4 years. In our study, especially in the patients with preoperative BMI of 45 to 55 kg/m 2 , the EWL at 12 and 24 months were 81.2% and 86.2%, respectively, and were similar to the study by Zaveri et al [36].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, especially in the patients with preoperative BMI ,45 kg/m 2 , the EWL at 12 and 24 months were higher than the ones reported by Pernaute et al [34]. Recently, a midterm outcome study on SADI-S by Zaveri et al [36] reported 77.6% and 85.9% EWL at 12 and 24 months, respectively, with the preoperative BMI of 49.8 kg/m 2 . These results continue in other studies without significant weight regain out to 4 years.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…There is not much difference in the operating time between both procedures, reflecting the improvement of our learning curve [13]. Multiple studies had investigated the effectiveness of SADI-S, RYGB, or biliopancreatic diversion with DS in unsuccessful LSG [14][15][16]. It was generally agreed that the mechanism of failure should guide the selection of the second procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures which take advantage of this scenario include the biliopancreatic diversion/duodenal switch. Based upon these previous observations and notions, more recent modifications to this malabsorption procedure have shown favorable results in treatment of metabolic diseases, with up to 4 years of follow up[ 66 , 67 ]. Further refinements in these procedures will likely yield more promising results which may be able to be individualized for specific patient needs.…”
Section: Bariatric Procedures Under Developmentmentioning
confidence: 99%